Theophylline impact on weaning in oxygen-dependent infants followed in an outpatient Kangaroo Program - Montealegre-Pomar, Adriana; Charpak, Nathalie; Lince-Rivera, Catalina (Frontiers in Pediatrics, 2024)
Background: theophylline was an orally administered xanthine used for treatment of apnea of prematurity and Bronchopulmonary Dysplasia in ambulatory follow-up of Low-Birth-Weight infants (LBWI) with oxygen-dependency in the outpatient Kangaroo Mother Care Program (KMCP). Theophylline's main metabolic product is caffeine; therefore, it was an alternative due to the frequent lack of ambulatory oral caffeine in low and middle-income countries. Objective: to assess the effectiveness of oral theophylline in decreasing days with oxygen and to describe frequency of adverse related events. Method: quasi-experiment before and after withdrawal of theophylline given systematically to LBWI with ambulatory oxygen in two KMCPs. Results: 729 patients were recruited; period 1: 319 infants when theophylline was given routinely and period 2: 410 infants when theophylline was no longer used. The theophylline cohort had less gestational age, less weight at birth, more days in Neonatal Intensive Care Unit, more days of oxygen-dependency at KMCP admission, and more frequencies of Intrauterine Growth Restriction and apneas. After adjusting with propensity score matching, multiple linear regression showed that nutrition was associated with days of oxygen-dependency, but theophylline treatment not. No differences were found in frequencies of readmissions up to 40 weeks, intraventricular hemorrhage or neurodevelopmental problems. Participants in period 2 had more tachycardia episodes. Conclusions: we did not find association between oral theophylline treatment and the reduction of days with ambulatory oxygen. For the current management of oxygen- dependency in LBW infants, the importance of nutrition based on exclusive breast feeding whenever possible, is the challenge.